A Cross-Sectional Study on the Prevalence of Footpad Dermatitis in Canadian Turkeys - Leishman, Emily M.; van Staaveren, Nienke; Osborne, Vern R.; Wood, Benjamin J.; Baes, Christine F.; Harlander-Matauschek, Alexandra (Frontiers in Animal Science, 2021)
Footpad dermatitis (FPD) can be a prevalent issue in commercial turkey production. This study aimed to identify the bird, housing, and management-related factors associated with the prevalence of FPD in Canadian turkey flocks. A questionnaire and flock health scoring system were developed and disseminated to approximately 500 commercial turkey farmers across Canada. Farmers were asked to score FPD on a subset of 30 birds within their flock using a 0-2 scoring scale based on severity. Prevalence of FPD in the flock was calculated as the percentage of affected birds (score 1 or 2). Multivariate linear regression modelling was used to identify factors associated with the prevalence of FPD. Four variables were included in the final model and accounted for 26.7% of the variation in FPD prevalence between flocks. FPD prevalence was higher with increasing bird weight (3.6 +/- 1.13), higher in flocks bedded with straw (12.1 +/- 7.9), higher in flocks where birds were picked up less frequently during daily inspections (11.6 +/- 8.10), and higher in flocks that used feed/water additives to reduce litter moisture (20.5 +/- 10.59). These findings are a preliminary exploratory assessment of risk factors related to FPD prevalence on Canadian turkey farms. While these findings emphasize the importance of litter management and the stockperson, estimates and P-values from this study should be interpreted with caution. Further longitudinal studies with the identified variables are required to better determine their influence on FPD.